L-R: ?, Calvert Pratt, Ewart A. Pratt, Yvonne (Rorke) Pratt, Patricia (Rorke) Yorke, ? - Rorke Family (1943)
Ewart A. Pratt and Yvonne (Rorke) Pratt, posing with their wedding party, including Patricia (Rorke) Yorke as maid of honour, and Ewart's brother Calvert. Cataloguer's title. Yvonne (Rorke) Pratt (1922-1998), youngest child of Kathleen (Forward) Rorke and James Rorke, was born on 4 June 1922. She was the granddaughter of James Addy Rorke and Ernest Edward Forward. Yvonne married Ewart A. Pratt (1919-2000), son of Calvert Coates Pratt and Agnes (Horwood) Pratt, on 30 October 1943 and had two children: Kathleen Agnes (Pratt) LeGrow and James Rorke Pratt (1949-2000). Yvonne died on 10 March 1998. Ewart died on 7 February 2000. Ewart's brother is Calvert (1921-2000), named after his father. Calvert died one month after his brother, 7 March 2000. Yvonne's sister is Patricia (Rorke) Yorke (1918- ). She was born on 17 March 1918. She married Howard K. Yorke (1912-ca. 1993) on 18 August 1945 and had a daughter, Lois Kathleen Yvonne. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.